2013
DOI: 10.1016/j.lithos.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Palaeomagnetic, geochronological and geochemical study of Mesoproterozoic Lakhna Dykes in the Bastar Craton, India: Implications for the Mesoproterozoic supercontinent

Abstract: 18 Palaeomagnetic analysis of the Lakhna Dykes (Bastar Craton, India) yields a palaeopole at 36.6°N, 19 132.8°E, dp=12.4°, dm=15.9°, and the U-Pb zircon age obtained from one of the rhyolitic dykes is 20 1466.4 ± 2.6 Ma (MSWD=0.21, concordia age based on two analyses with identical Pb/U ages), 21 similar to previously published U-Pb ages. Major and trace element analyses of the Lakhna Dykes 22 30 2 model. Our preferred reconstruction implies a long Palaeo-to Mesoproterozoic accretionary orogen 31 stretching fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(57 citation statements)
references
References 122 publications
(4 reference statements)
3
53
0
1
Order By: Relevance
“…India suggest it was tied to Baltica within the Nuna supercontinent (Pisarevsky et al, 2013;Pisarevsky et al, 2014). In this paleomagnetically constrained reconstruction, the Dharwar Baltica separated between 1120-1080 Ma (Pisarevsky et al, 2013).…”
Section: A New Paleomagnetic Pole For the 1466 Ma Lakhna Dykes From Tmentioning
confidence: 74%
See 1 more Smart Citation
“…India suggest it was tied to Baltica within the Nuna supercontinent (Pisarevsky et al, 2013;Pisarevsky et al, 2014). In this paleomagnetically constrained reconstruction, the Dharwar Baltica separated between 1120-1080 Ma (Pisarevsky et al, 2013).…”
Section: A New Paleomagnetic Pole For the 1466 Ma Lakhna Dykes From Tmentioning
confidence: 74%
“…In this paleomagnetically constrained reconstruction, the Dharwar Baltica separated between 1120-1080 Ma (Pisarevsky et al, 2013). Geological evidence for this breakup event is limited due to subsequent overprinting events but data from southern…”
Section: A New Paleomagnetic Pole For the 1466 Ma Lakhna Dykes From Tmentioning
confidence: 93%
“…Although, early Precambrian mafic dykes are well exposed in the southern parts of the Bastar craton (Srivastava et al, 2016), they have also been encountered in the middle (Srivastava and Gautam, 2012) and the northern (Pisarevsky et al, 2013;Srivastava and Gautam, 2015) parts of the Bastar craton. Pisarevsky et al (2013) have presented paleomagnetic, geochronological and geochemical data on the ~N-S trending Mesoproterozoic Lakhna dykes from the northern Bastar craton. Petrographically and geochemically Lakhna dykes show variation from alkaline (trachyte), felsic (rhyolite) to mafic (dolerite) derivatives.…”
Section: N V Chalapathi Rao and Rajesh K Srivastavamentioning
confidence: 99%
“…The reconstructions are highly speculative and sometimes technically incorrect mainly due to paucity of high-quality Late Palaeoproterozoic and Mesoproterozoic palaeomagnetic data. The data are insufficient even to draw an apparent polar wander (APW) path for any single craton 12 .…”
mentioning
confidence: 99%
“…These results are restricted to the early-middle Palaeoproterozoic Era. The only study that pertains to the Late Palaeoproterozoic to Mesoproterozoic eras has been done by Pisarevsky et al 12 from dykes yielding a U-Pb age of 1466.4  2.6 Ma on the Bastar craton. The authors reported steep upward/downward magnetization directions from these dykes.…”
mentioning
confidence: 99%